1988
DOI: 10.1002/j.1460-2075.1988.tb03096.x
|View full text |Cite
|
Sign up to set email alerts
|

A cell-specific activator in the Xenopus A2 vitellogenin gene: promoter elements functioning with rat liver nuclear extracts.

Abstract: Transfection experiments using Xenopus vitellogenin A2 gene constructs allowed us to identify an activator which increases the activity of the thymidine kinase promoter. The activator is located between −121 and −87 of the A2 vitellogenin gene and is separated by a stretch of curved DNA from the estrogen‐responsive DNA element at −331. The activator functions in a cell‐specific manner, as it is active in human breast cancer cells (MCF‐7) as well as hepatoma cells but not in fibroblasts or HeLa cells. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
4
32
0
Order By: Relevance
“…The fact that three of the four factor-binding sites identified in the present study correspond to sites that were previously shown to be footprinted in vivo in response to estrogen (31) indicates that our results are very probably relevant to the normal regulation of this gene. A comparison of these results with data recently reported for the frog vitellogenin gene promoters (11,13) suggests that vitellogenin promoters have evolved much more than might have been predicted on the basis of sequence comparisons alone.…”
supporting
confidence: 60%
“…The fact that three of the four factor-binding sites identified in the present study correspond to sites that were previously shown to be footprinted in vivo in response to estrogen (31) indicates that our results are very probably relevant to the normal regulation of this gene. A comparison of these results with data recently reported for the frog vitellogenin gene promoters (11,13) suggests that vitellogenin promoters have evolved much more than might have been predicted on the basis of sequence comparisons alone.…”
supporting
confidence: 60%
“…Several TATA-box-containing promoters have a bent DNA structure upstream of the TATAbox. 12,36,48) The helix trajectories of 504 vertebrate promoters indicate that all regions containing a TATAbox (either canonical or non-canonical) form curved DNA structures, 49) suggesting that intrinsic DNA curvature is important in the recognition of the TATA-box by TATA-box binding protein, TBP.…”
Section: Sequence Analysis Of the C3-22 Amplicon Bent Dna Sitesmentioning
confidence: 99%
“…In Vitro Transcription-In vitro transcription reactions contained 6 l of rat liver nuclear extract (6.3 g/l) prepared as described by Döbbeling et al (32). E. coli mock extract, recombinant MH 6 -hPR(DBD), and recombinant MH 6 -hPR0 added to some of the reactions were expressed in E. coli or Sf21 cells infected with recombinant baculovirus, respectively, and purified as described above.…”
Section: Hpr-dtaf II 110 Interactionmentioning
confidence: 99%